Elevação sem motivação aparente das vogais médias pretônicas entre os jovens porto-alegrenses - Silva, Ana Paula Correa da (2014)
This study aims to analyze the variable raising of pretonic mid vowels with no apparent motivation in the Portuguese variety spoken by youths from Porto Alegre, as in s[e]nhor ~ s[i]nhor and g[o]verno ~ g[u]verno. In order to investigate the process, we started from the premises of the Variation Theory (LABOV, 1972, 1994, 2001). As the theory revealed to be limited in explaining the process, we adopted the Lexical Diffusion Theory (CHEN, WANG, 1975; OLIVEIRA, 1991, 1992, 1995) as well as the Exemplar Theory (JOHNSON, 1997; PIERREHUMBERT, 2001, 2003) premises. The sample analyzed, extracted from VARSUL (Linguistic Variation in Southern Brazil) database and collected in 2004, consists of 17 youths (9 men and 8 women) between 16 and 23 years-old. Raising application rates in frequent lexical words were 3% (N = 1.268) for /o/ vowel and 2% (N = 1.562) for /e/ vowel, confirming the expected low application rates (KLUNCK, 2007; BISOL, 2009; CRUZ, 2010). Results indicated that raising without apparent motivation is not governed by a specific segmental and/or prosodic conditioning factor. The lexical items were significant to the raising of the pretonic mid vowels indicating that the process is of lexical nature. Finally, social variables were not relevant to the raising application.